Analysis of the Behaviour of Immunoglobulin G Antibodies in Children and Adults Convalescing From Severe Acute Respiratory Syndrome-Coronavirus-2 Infection - Márquez-González, Horacio; López-Martínez, Briceida; Parra-Ortega, Israel; Rosa-Zamboni, Daniela de la; Salazar-García, Marcela; Olivar-López, Victor; Klünder-Klünder, Miguel (Frontiers in Pediatrics, 2021)
The pandemic caused by SARS CoV-2 (COVID-19) has affected millions of people since 2020. There are clinical differences and in mortality between the adult and pediatric population. Recently, the immune response through the development of antibodies has gained relevance due to the risk of reinfection and vaccines' development. Objective: The objective of this study is to identify and describe the development of IgG antibodies against SARS-CoV-2 in pediatric and adult patients with a history of positive reverse transcriptase-polymerase chain reaction (RT-PCR) results Methods: Cross-sectional observational study carried out in a Pediatric Hospital in Mexico City included patients under 18 years of age and health personnel with positive RT-PCR for COVID-19comparing antibody expression. The development of specific IgG antibodies was measured, the presence of comorbidities, duration, and severity of symptoms was determined. Results: 61 subjects (20 <18 years and 41> 18 years) were analyzed. The median sample collection was three weeks. There were no differences in the expression of specific antibodies; no differences were shown according to the symptoms' severity. A positive correlation (r = 0.77) was demonstrated between the duration of symptoms and antibody levels. Conclusions: In conclusion, there is a clear association between the duration of the symptoms associated with SARS-CoV-2 infection and the IgG units generated in pediatric and adult patients convalescing from COVID-19.